2012
DOI: 10.1155/2012/586491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Temperature onCapnodis tenebrionisAdult Phenology

Abstract: The phenology of Capnodis tenebrionis adults was presented with reference to two different climate conditions. In a temperate moderate-warm climate, adult density showed two separate peaks during the year: one in early summer of the overwintering generation and one with beetles emerging in the late summer. In a warmer semiarid climate, the overwintering adults and the new generation overlapped during summer with a continuous increase of adult density. The difference in the average annual temperature between ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Host phenology model and emergence of parasitoid species. Many previous studies have suggested linear and nonlinear equations for describing the rate of insect development and population dynamics (Bonsignore, 2012;Damos & Savopoulou-Soultani, 2012). In the present study, we used a nonlinear logistic equation (four-parameter regression model) with value coefficients obtained from all the datasets (2 years and three fields) for the cumulative percentage of each stage examined.…”
Section: Discussionmentioning
confidence: 99%
“…Host phenology model and emergence of parasitoid species. Many previous studies have suggested linear and nonlinear equations for describing the rate of insect development and population dynamics (Bonsignore, 2012;Damos & Savopoulou-Soultani, 2012). In the present study, we used a nonlinear logistic equation (four-parameter regression model) with value coefficients obtained from all the datasets (2 years and three fields) for the cumulative percentage of each stage examined.…”
Section: Discussionmentioning
confidence: 99%
“…Abundance, distribution and phenology of poikilotherm species are dependent on environmental and mostly climatic conditions (Hodar and Zamora ; Nahrung et al. ; Bonsignore ). In particular, variations in ambient temperature regulate fundamental biological processes such as reproduction and growth (Larsson and Kustvall ; Horton et al.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal adaptations of organisms are crucial for their survival and functioning in ecosystems. Abundance, distribution and phenology of poikilotherm species are dependent on environmental and mostly climatic conditions (Hodar and Zamora 2004;Nahrung et al 2008;Bonsignore 2012). In particular, variations in ambient temperature regulate fundamental biological processes such as reproduction and growth (Larsson and Kustvall 1990;Horton et al 2002;Norgate et al 2010;Damos 2012;R egni ere et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…C. tenebrionis overwinters as both larvae and adults. The overwintering generation commences adult emergence in spring coinciding with a rise in ambient temperature (Bonsignore et al, 2008); the new generation of adult offspring begins emerging in summer (Bonsignore, 2012).…”
Section: Introductionmentioning
confidence: 99%